2016
DOI: 10.1007/s13201-016-0474-4
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of agriculture field water for improving membrane flux during pesticide removal

Abstract: Pretreatment of feed water to improve membrane flux during filtration of agriculture field water containing substituted phenyl urea pesticide diuron has been reported. Laboratory-made reverse osmosis membrane was used for filtration. Preliminary experiments were conducted with model solution containing natural organic matter extracted from commercial humic acids, divalent ions Ca 2? , Mg 2?. Membrane fouling was characterized by pure water flux decline, change in membrane hydrophilicity and infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…TSS removal in feed water prior to a membrane filtration treatment process is important to improve membrane flux [ 35 ]; especially for highly polluted wastewater such as the one generated from the poultry slaughterhouse activities. In the raw wastewater, minimum, maximum, and average recorded TSS concentrations were 116.00, 1068.00, and 452.67 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…TSS removal in feed water prior to a membrane filtration treatment process is important to improve membrane flux [ 35 ]; especially for highly polluted wastewater such as the one generated from the poultry slaughterhouse activities. In the raw wastewater, minimum, maximum, and average recorded TSS concentrations were 116.00, 1068.00, and 452.67 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that humic acid had less influence on pesticide rejection in deionized water due to the absence of ions, hence fouling was less than 6 % [42]. When the feed solution was switched to field water in a more recent study, there was a substantial increment in membrane fouling (14 %) [50]. The fouling was further aggravated to 23 % and 30 % when magnesium and calcium were added.…”
Section: Presence Of Trace Organic Mattersmentioning
confidence: 97%
“…Figure 5 suggests that significant competitive interactions took place between the NOM, BaP molecules, and the adsorbent leading to the comparative decline in removal efficiency, Freundlich adsorption capacity (K f ), partition coefficient (K d ), and maximum adsorption capacity (q max ). NOM has been reported to cause fouling of membranes, and retention of hydrophobic compounds and metals in solution, thus limiting the efficiency of conventional water treatment plants (Mehta et al 2017;Kurwadkar et al 2019;Adeola & Forbes 2021b). Essentially, NOM often alters the solution's chemistry such as pH, ionic strength, and the presence of leachable trace and heavy metals (Fig.…”
Section: Influence Of Nom On Sorbent-sorbate Interactionmentioning
confidence: 99%